Two dimensional modeling of a membrane reactor for ATR of methane - Rodriguez, Maria Laura (2012)
A theoretical study of a multitubular membrane reactor for the autothermal reforming of methane over a Ni/Al2O3 catalyst is presented. A 2-D model is selected to account for the strong composition and temperature gradients along the axial and radial coordinates. The effect of the degree of reduction of the Ni catalyst on the reforming reaction rates is taken into account in the model. The influence of the main operating conditions on the reactor behavior is studied. The results suggest that the membrane reactor is a promising alternative to carry out ATR of methane at milder conditions than those commonly found in a conventional reactor. The axial distribution of the O2 fed to the reactor is a powerful tool to influence the axial temperature profiles. Nevertheless, a careful design is necessary to avoid risky conditions such as oxygen accumulation in the tubes.